GEOCHRONOLOGICAL AND GEOCHEMICAL STUDIES ON THE BOROHORO PLUTONS, NORTH OF YILI, NW TIANSHAN AND THEIR TECTONIC IMPLICATION - Wang B.; Shu L.S.; Cluzel D.; Faure M.; Charvet J. (My University, 2007)
Hercynian Borohoro plutons extending SE-NW along the northern margin of Yili Block develop in a wide area of more than 2000km2. It is predominantly composed of dark gabbroid diorite, light-coloured biotite granite and pink biotite K-granite. U-Pb La-ICP-MS dating on zircons yields 301 ± 7Ma for gabbroid diorite, 294 ± 7Ma to 285 ± 7Ma for light-coloured biotite granite and 280 ± Ma to 266 ± 6Ma for biotite K-granite, respectively. Geochemical analyses suggest that the Boroboro plutons are mainly subaluminous I-type granite with minor aluminous S-type granite. They have higher components of LREE than HREE, and dissimilar REE distribution patterns of granitoids from two sections indicate that they were probably derived from different magma sources, further isotopic study is in urgent need. These granites are rich in K, Rb, Th and Ba, and depleted in Nh, Ta, Zr and Hf with respect to Ocean Ridge Granite. Trace element discriminations suggest that these granitic rocks formed in a subduction-related volcanic arc setting. Comparing to the previous results, this study proposes that the Borohoro plutons were resulted from south-directed subductionary orogeny of an oceanic basin in North Tianshan, the convergent process was completed in Middle Permian, and was followed by intra-continental orogeny and subsequent extension in Late Permian.
Keywords: GRANITE; TIANSHAN BELT; TRACE ELEMENT GEOCHEMISTRY; YILI BLOCK; ZIRCON U-PB DATING; Paleozoic::Permian; Палеозой::Пермская